Architecture in flux - Paramita, Kristanti Dewi (Department of Architecture Faculty of Engineering Universitas Indonesia, 2025)
Architecture exists in flux, shaped by the rapid social, cultural, and environmental transformation in current society. The articles in this edition of ARSNET explore various contexts and design methodologies that emerge amidst such rapid and often disruptive changes. The study discusses different conditions produced by such changes, from the inevitability of time that leads to deterioration, environmental pressures that create separation from nature, to high rates of urbanisation that led to limitation of living space and changes to users' livelihood. Discussions elaborated in this edition outline how architecture in flux may lead to alternative design approaches. These approaches range from construction practices that celebrate impermanence; design operations that value neglected, incomplete, and hidden areas; architecture that calls for reconnection with nature; to exploration of adaptive and inclusive objects and spatialities for multiplicities of users. In doing so, this edition highlights the changing processes and relationships of the built environment in the state of flux, towards architecture that continuously evolves and celebrates change.